Malaysian currency crisis: how and why it happened - Mahathir Mohamad (Subang Jaya: Pelanduk Publications, 2000)
A detailed exp. of how M'sia handled the economic & financial turmoil
Includes index
Keywords: Foreign exchange -- Malaysia; Devaluation of currency -- Malaysia; Financial crises -- Malaysia